The role of autoimmunity in vascular dementia - (:unkn) unknown (KARGER, 1996)
It is now known that immunologic mechanisms have a role in the initiation of atherosclerotic processes. No antibodies against vascular endothelial cell (VEC) specific antigenic systems have been demonstrated in the pathogenesis of small vessel (lacunar) infarcts, though autoantibodies have been detected in 80% of patients with multi-infarct dementia. We studied VEC-specific antibodies in 17 patients with a diagnosis of vascular dementia; in 17 nondemented patients with small vessel infarcts and in 16 healthy, nondemented control group patients by using the Terasaki microtoxicity method. All three groups were correlated according to known risk factors. VEC-specific antibodies were positive in 94% demented patients, whereas no antibodies were detected in patients with small vessel infarcts or in the control group. This result may suggest the existence of an immunologic mechanism in the etiopathogenesis of vascular dementia differing form small vessel infarcts.
Keywords: endothelial cell; autoimmunity; ATHEROGENESIS; DIAGNOSIS; CRITERIA; SYSTEM